ORGANIZATIONAL CLIMATE AND TEACHER PEDAGOGIC COMPETENCE ON QUALITY OF SERVICES IN SMP - Hamid AL JUFRI; Dwi PRIYONO (Journal of Education and Leadership in Education, 2018)
This study aims to determine the influence of Organization Climate and Teacher Pedagogic Competence School Quality Service in Public Junior High School District Kembangan in West Jakarta.This study is descriptive in the entire population of teachers in Public Junior High School in West Jakarta District of New Kebayoran as many as 7 State Primary School with a number of teachers is 347, elected by proportional random sampling, the number of 186 teachers. Data was collected using a questionnaire to measure the Organization Climate, Teachers and Achievement Motivation Teacher on School Quality Service.The results showed that: first, there are positive Influence of Total Quality Management to Principal Teacher School Quality Service is acceptable, it can be determined by t test calculations in which th> tt (40.38> 1.66). And based on the calculation formula product moment correlation coefficient can be determined path coefficients (p31 = 0.272) at α = 0.05, that rh> rt (0.948 > 0.148) means that it can be said that there are positive effects of TQM Head Teacher School Quality Service, by r213 = coefficient of determination of 0.8986. This means that 89.89% of the variation of Teacher School Quality Service (X3) are affected by TQM Principal (X1). Second, there is a positive influence on Achievement Motivation Teacher Teacher School Quality Service is acceptable, it can be determined by t test calculations in which th> tt (73.92> 1.66). Third, there is a positive influence Principal Total Quality Management (X1) of the Teacher Achievement Motivation (X2) can be accepted, it can be determined by t test calculations in which th> tt (32.31 > 1.66).